2010
DOI: 10.1007/978-3-642-15892-6_23
|View full text |Cite
|
Sign up to set email alerts
|

How Our Personality Shapes Our Interactions with Virtual Characters - Implications for Research and Development

Abstract: Abstract. There is a general lack of awareness for the influence of users´ personality traits on human-agent-interaction (HAI). Numerous studies do not even consider explanatory variables like age and gender although they are easily accessible. The present study focuses on explaining the occurrence of social effects in HAI. Apart from the original manipulation of the study we assessed the users´ personality traits. Results show that participants´ personality traits influenced their subjective feeling after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 28 publications
(27 reference statements)
4
25
0
Order By: Relevance
“…A follow up big 5 personality test [23,24] shows that these two subjects are less extroverted as their test scores are in percentile 24% and 8% in a data groups with 711 users examined in [25]. This might suggest that whether people prefer mimicry is related to individual personality which supports von der Pütten et al's findings [26]: participants' personality traits influence their subjective feeling and evaluation of virtual characters.…”
Section: Experiments 1: Preference For Self-similar Motionmentioning
confidence: 52%
“…A follow up big 5 personality test [23,24] shows that these two subjects are less extroverted as their test scores are in percentile 24% and 8% in a data groups with 711 users examined in [25]. This might suggest that whether people prefer mimicry is related to individual personality which supports von der Pütten et al's findings [26]: participants' personality traits influence their subjective feeling and evaluation of virtual characters.…”
Section: Experiments 1: Preference For Self-similar Motionmentioning
confidence: 52%
“…For visual nonverbal displays we studied the literature on displays of attitude in initial human-human interactions (interactions where the interaction partners meet for the first time). Then, given the fact that previous research has shown how personality traits of extraversion and agreableness are important predictors of HAI [28], we also take into account findings on nonverbal cues which are important for predicting personality traits.…”
Section: Cue Extractionmentioning
confidence: 99%
“…In [28], two conditions (low and high behaviour realism) of an agent designed to build rapport (the Rapport agent) were manipulated in interaction with humans. Further, human personality traits were correlated with persistent behavioral patterns, such as shyness or fear of interpersonal encounters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Von der Pütten et al (2010) show that differences in gesture rate and gesture performance parameters significantly change the perception of extraversion.…”
Section: Virtual Agents and Personalitymentioning
confidence: 99%